Therianthropes in a Cartesian and an Animistic Cosmology: Beyond-the-Pale Monsters versus Being-in-the World Others - Guenther, Mathias (Literatura Ludowa. Journal of Folklore and Popular Culture, 2022)
The nature of human-animal hybrid beings (or therianthropes) is examined in an Animistic (traditional San Bushman) and a Cartesian (Early Modern Western) cosmology. In each ontological ambiguity is imagined and conceptualized in different terms. One of them is through monstrosity, which, in the Western schema, is equated with human-animal hybridity. This equivalence threatens the boundaries and categories that buttress western cosmology, through a being – the human-animal hybrid – deemed a conceptual and epistemological abomination. It elicits a category crisis that is as much cerebral as it is visceral as the were-beings it conceives are feared and demonized. No such valences attach to therianthropes in the cosmology described in this paper. It is an “entangled” cosmology shot through with ambiguity and fluidity in which human-animal hybridity is neither abominable nor feared. Instead, as a pervasive and salient theme of San world view and lifeways, especially its expressive and ritual spheres, along with hunting, ontological mutability becomes an integral component of people’s thoughts and lives and thereby normalized and naturalized. Beings partaking of this state are deemed another species of being with whom humans engage as other-than-humans, on shared social terms. Monsters are beings who negate or transgress the moral foundation of the social order. San monstrosity, conceptually and phenomenologically, becomes thereby a matter of deviation from social (moral) pre/proscriptions rather than from classificatory (ontological) ones. This basic conceptual difference notwithstanding, we also find a fundamental commonality: the inversion, through monsters and monstrosity, of each cosmology’s underlying epistemic matrices, of structure and ambiguity, respectively.